STRATEGI PENGEMBANGAN SURABAYA ART EVENT (SAE) - Heri Wijayanto (Melayu Arts and Performance Journal, 2018)
ABSTRACT This article aims at analyzing the internal and external factors of Surabaya Art Event (SAE) as an effort in making the strategy of organizational development. The existence of many Event Organizers (EO) results in a more competitive competition. Hence it’s needed the understanding of the internal and external factors. Three internal members of SAE became interviewees interviewed to determine the rank of every indicator. Its result shows that SAE developed the Hold and Maintain strategy. The general strategy used is market penetration and product development. It’s needed the selection of strategy namely the use of every strength to face every threat by creating diversification in order to create opportunity. Keywords: strategy, development, surabaya art event  ABSTRAK Artikel ini bertujuan untuk menganalisis faktor internal dan eksternal SAE sebagai upaya dalam rangka membuat strategi dalam pengembangan organisasi. Banyaknya EO berdampak pada persaingan yang lebih kompetitif. Hal ini menyebabkan perlunya pemahaman terhadap faktor internal dan eksternal. Tiga orang anggota internal SAE dijadikan sebagai narasumber diwawancarai untuk menentukan peringkat setiap indikator. Hasilnya menunjukan bahwa SAE mengembangkan strategi Hold and Maintain (pertahankan dan pelihara). Strategi umum yang dipakai adalah penetrasi pasar dan pengembangan produk. Diperlukan pemilihan strategi yang berupa penggunaan setiap kekuatan untuk menghadapi setiap ancaman dengan menciptakan diversifikasi untuk menciptakan peluang.